2010
DOI: 10.1007/s00439-010-0928-y
|View full text |Cite
|
Sign up to set email alerts
|

Potential involvement of more than one locus in trait manifestation for individuals with Leber congenital amaurosis

Abstract: Leber congenital amaurosis (LCA) is a clinically and genetically heterogeneous retinal dystrophy. The causes of LCA have been unraveled partially at the molecular level. At least 14 genes have been reported that, when mutated, result in LCA. To understand the roles of the known genes in LCA, a group of outbred subjects from 60 apparently either recessive families, with one or more affected individuals, or isolated patients were evaluated. One affected individual from each family underwent comprehensive mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 46 publications
(70 reference statements)
1
13
0
Order By: Relevance
“…A recent selective screen of 13 LCA genes in 60 affected subjects revealed a striking 43% of the mutant alleles in Cep290 (24), suggesting a significant contribution of this gene to retinal disease manifestation. In addition, mutations in Cep290 produce varying clinical outcomes of JBTS (25)(26)(27), MKS (28)(29)(30), and BBS (31).…”
Section: Introductionmentioning
confidence: 99%
“…A recent selective screen of 13 LCA genes in 60 affected subjects revealed a striking 43% of the mutant alleles in Cep290 (24), suggesting a significant contribution of this gene to retinal disease manifestation. In addition, mutations in Cep290 produce varying clinical outcomes of JBTS (25)(26)(27), MKS (28)(29)(30), and BBS (31).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of variants in multiple LCA genes has previously been reported. 12,37 So far, it is unclear whether they influence disease penetrance or represent modifying alleles. Undoubtedly, application of MPS-based strategies on a large scale will reveal more insights into the understanding of intra-and interfamilial variability, individual phenotypes, and a patient's visual prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…This clinically and genetically heterogenous disease is caused by mutations in at least 16 genes (Table 1), with mutations in the CEP290 gene being the most common cause of LCA. Mutations in CEP290 can also cause other ciliopathies, including Joubert syndrome, Meckel-Gruber syndrome, and BBS (6). While extending their previous work on LCA (7), Rachel et al (3) found that almost 10% of individuals with LCA have a mutation in MKKS, a gene also found mutated in individuals with MKKS and BBS.…”
Section: Cilia -The Basicsmentioning
confidence: 92%
“…Specifically, activation of the ATR/Chk1 pathway during replication stress both prevents collapse of troubled replication forks into DNA double-strand breaks and inhibits cell-cycle progression into M phase. Previous culture-based studies have demonstrated that suppressing the G 2 -M phase checkpoint through ATR and Chk1 inhibition is particularly toxic when combined with loss of G 1 -S checkpoint function via p53 deficiency (4)(5)(6)(7)(8)(9). This dual loss produces a checkpoint short circuit ( Figure 1A).…”
Section: Targeting Chk1 In An Advanced Experimental Model Of Tnbcmentioning
confidence: 95%
See 1 more Smart Citation